Zat Warna Untuk Kulit - Maria Maria (Jurnal Kimia dan Kemasan, 1985)
Leather dyestuffs can be divided into the two main classes i.e. naturaland synthetic dyestuffs. Natural dyestuffs, that are obtained from animal or vegetable-matter. Synthetic dyestuffs can be prepared synthetically. The best dyestuffs consist of leather affinity and dyes. If the leather is not reactioned perfectly with dyes who is not suitable, it will be difficulty, for example pale colour, is not good shade, in equal dyestuffs etc.